Activation of Ge−H and Sn−H Bonds with N‐Heterocyclic Carbenes and a Cyclic (Alkyl)(amino)carbene. Issue 3 (24th November 2022) - Philipp, Michael S. M.; Bertermann, Rüdiger; Radius, Udo
Abstract: A study of the reactivity of several N‐heterocyclic carbenes (NHCs) and the cyclic (alkyl)(amino)carbene 1‐(2, 6‐di‐ iso ‐propylphenyl)‐3, 3, 5, 5‐tetramethyl‐pyrrolidin‐2‐ylidene (cAAC Me ) with the group 14 hydrides GeH2 Mes2 and SnH2 Me2 (Me=CH3, Mes=1, 3, 5‐(CH3 )3 C6 H2 ) is presented. The reaction of GeH2 Mes2 with cAAC Me led to the insertion of cAAC Me into one Ge−H bond to give cAAC Me H−GeHMes2 (1 ). If 1, 3, 4, 5‐tetramethyl‐imidazolin‐2‐ylidene (Me2 Im Me ) was used as the carbene, NHC‐mediated dehydrogenative coupling occurred, which led to the NHC‐stabilized germylene Me2 Im Me ⋅GeMes2 (2 ). The reaction of SnH2 Me2 with cAAC Me also afforded the insertion product cAAC Me H−SnHMe2 (3 ), and reaction of two equivalents Me2 Im Me with SnH2 Me2 gave the NHC‐stabilized stannylene Me2 Im Me ⋅SnMe2 (4 ). If the sterically more demanding NHCs Me2 Im Me, 1, 3‐di‐ iso propyl‐4, 5‐dimethyl‐imidazolin‐2‐ylidene ( i Pr2 Im Me ) and 1, 3‐bis‐(2, 6‐di‐ iso propylphenyl)‐imidazolin‐2‐ylidene (Dipp2 Im) were employed, selective formation of cyclic oligomers (SnMe2 ) n (5 ; n =5–8) in high yield was observed. These cyclic oligomers were also obtained from the controlled decomposition of cAAC Me H−SnHMe2 (3 ). Abstract : Insertion of cAAC Me into E−H bonds of EH2 R2 (E=Ge, R=Mes; E=Sn, R=Me) to yield cAAC Me H−EHR2 and the dehydrogenative coupling of EH2 R2 using N‐Heterocyclic Carbenes are reported.